Model Transformation of Platform Specific Model to Vanilla Model – A Proposed Platform Independent Model for Declarative User Interface. - Agarwal, Smita; Aggarwal, Alok; Dixit, S; Kumart, Adarsh (International Journal of Computer Sciences and Engineering, 2025)
In classic software re-engineering, the user interface are considered to be Platform Specific. Hence were always excluded from the process of software re-engineering. The user interface were re-written for the target platform and integrated with business application in the end. In this paper we propose a Vanilla Model – A Platform Independent Model for Declarative User Interface and algorithm for model transformation using Vanilla Model for Declarative User Interface. This approach will preserve the source artifact user interface will make re-engineering user interface part of main process,. This transformation is then applied to five of the popular libraries such as SWING, HTML5, and more recent libraries of Android and Python- Tkinter